(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
This scientific article examines the technologies and approaches for optimizing the vehicle maintenance (VM) system to improve the operational efficiency of motor vehicles in Termiz city. The study identifies key factors affecting vehicle performance, fuel consumption, service life, and operational costs. Analysis shows that modern automated technologies, digital monitoring systems, and regular diagnostic maintenance significantly enhance vehicle efficiency, reduce fuel consumption by 10–15%, extend engine service life by 15–20%, and decrease emissions. The research also emphasizes the importance of standardizing maintenance procedures, improving staff qualifications, and integrating high-performance technologies into the maintenance process. The results provide practical recommendations for improving vehicle operation efficiency, ensuring technical safety, and contributing to the ecological sustainability of urban transport.